2020
DOI: 10.1093/ajcn/nqaa135
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inflammatory Index and metabolic syndrome in Mexican adult population

Abstract: Background Evidence suggests low-grade inflammation as the cause of metabolic syndrome and suggests diet as a promoter of chronic inflammation. Objective We evaluated the association between inflammatory diets and the development of metabolic syndrome in Mexican adults. Methods A total of 399 participants of the Health Workers Cohort Study were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 32 publications
13
48
1
Order By: Relevance
“…The E-DII score range (−4.89 to 4.45) recorded for the Ecuadorian women in the sample was similar to those recorded for other Latin American studies examining the association of E-DII scores with Mets and/or cardiometabolic components in Bogota, Colombia (−3.71 to 3.64) [ 34 ], Cuernavaca and Toluca, Mexico (−4.5 to 3.8) [ 35 ], Mexico City (−5.49 to 4.12 [ 36 ] and Ribeirao Preto, Brazil (−4.69 to 5.28) [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The E-DII score range (−4.89 to 4.45) recorded for the Ecuadorian women in the sample was similar to those recorded for other Latin American studies examining the association of E-DII scores with Mets and/or cardiometabolic components in Bogota, Colombia (−3.71 to 3.64) [ 34 ], Cuernavaca and Toluca, Mexico (−4.5 to 3.8) [ 35 ], Mexico City (−5.49 to 4.12 [ 36 ] and Ribeirao Preto, Brazil (−4.69 to 5.28) [ 33 ].…”
Section: Discussionsupporting
confidence: 81%
“…Cohort and cross-sectional studies investigating the association between energy-adjusted Dietary Inflammatory Index E-DII scores with MetS and/or individual cardiometabolic risk biomarkers have reported mixed findings for diverse populations from North America [ 20 , 21 , 22 ], Europe [ 23 , 24 , 25 , 26 , 27 , 28 ], Asia and the Middle East [ 29 , 30 , 31 , 32 ]. Published studies reporting on association of E-DII scores with MetS and/or cardiometabolic risk components in Latin American adults are limited to three countries, i.e., Brazil [ 33 ], Colombia [ 34 ] and Mexico [ 35 , 36 ] and their findings also are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Results for this cytokine remain controversial in children; some studies in non-Hispanic children have also reported no associations [58] while others have reported a significant positive association [59]. Moreover, a recent study in Mexican adults found, over a period of 13 years, a positive association between the highest quartile of DII and the incidence of metabolic syndrome (HRQ4vsQ1 = 1.99; 95% CI: 1.03, 3.85; P-trend = 0.04), particularly associated with hypertriglyceridemia, hypertension and abdominal obesity [60]. Even though in that study cytokines and adipokines were not assessed, it supports the utility and importance of earlier evaluations in childhood to prevent metabolic and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 97%
“…A population-based multi case–control study in Spain ( 39 ) showed that a one-unit DII score increment is associated with increased colorectal cancer risk. A meta-analysis of prospective studies ( 10 ), including more than 28,000 participants, reported an association between DII and elevated risk of cancer, although the dose–response association requires further investigation. However, the selected meta-analyses examining the above associations have some limitations, such as the substantial heterogeneity, the 95% PI containing the null value, and the presence of small-study effects and excess significance bias.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the DII offers a valid and readily comparable method for evaluating individuals' dietary inflammatory potential according to the pro- and anti-inflammatory aspects of the overall diet ( 7 ). In recent years, the role of DII in relation to non-communicable diseases, including cardiovascular disease (CVD) ( 8 , 9 ), metabolic syndrome ( 10 ), and various types of cancer ( 11 ), has been examined in the epidemiological literature. According to the consensus, higher DII scores are deleterious to health.…”
Section: Introductionmentioning
confidence: 99%